The impact of self-efficacy on substance use in nursing students: the mediating role of sense of coherence - Daria Schneider-Matyka; Anna Maria Cybulska; Mariusz Panczyk; Anna Andruszkiewicz; Danuta Dyk; Aleksandra Gaworska-Krzemińska; Agnieszka Gniadek; Dorota Kozieł; Ewa Kupcewicz; Agnieszka Młynarska; Jolanta Lewko; Barbara Ślusarska; et al. (BMC Nursing)
Abstract Background Substance use among university students, particularly nursing students, poses significant health and professional risks. Alcohol and psychoactive substance use can impact academic performance and future clinical practice. Self-efficacy and sense of coherence (SOC) are psychological constructs that influence behavior and coping mechanisms. This study investigates the mediating role of SOC in the relationship between self-efficacy and substance use among nursing students. Methods A cross-sectional observational study was conducted among 2,689 nursing students from multiple universities in Poland. Data collection utilized standardized tools, including the Sense of Coherence-29 Scale, Generalized Self-Efficacy Scale, AUDIT (Alcohol Use Disorders Identification Test), and CRAFFT (screening tool for psychoactive substance use). Statistical analyses involved mediation modeling using Hayes’ PROCESS macro, with bootstrapping (5,000 resamples) to assess indirect effects. Results No direct relationship was found between self-efficacy and alcohol or psychoactive substance use. However, SOC mediated the relationship between self-efficacy and psychoactive substance use, particularly through the comprehensibility component of SOC. First-year students exhibited a stronger mediating effect, suggesting that early university experiences influence the interplay between self-efficacy and substance use. The mediating effect decreased in later years, indicating adaptation to academic and social environments. Conclusions SOC, particularly comprehensibility, plays a crucial role in linking self-efficacy to substance use behaviors in nursing students. Strengthening SOC through targeted interventions may help mitigate risky behaviors and improve overall well-being. Educational programs focusing on resilience, stress management, and coherence-building strategies could be beneficial for nursing students to support their future professional roles. Clinical trial number Not applicable.